2021
DOI: 10.3389/feart.2021.625926
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Late Holocene Storm Deposit From Shore-normal Beach Sediments From the Gulf of Thailand

Abstract: Grain size, as one of sedimentological proxies, coupled with a detailed description of the sedimentary structures and luminescence dating were used to unveil the sediment sources and transport process of the Holocene ancient coastal storm events recorded in the beach ridge plain, wet swale and muddy environments at Prachuap Khiri Khan, in the Southern Peninsula of Thailand. In this study, a total of 141 sand samples were collected from the shore-normal ridge-swale topography and analyzed for layers of candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The parallel-laminated, inclined-laminated sand, and normal and reverse grading found in Units II, IV, and VI (Figures 3, 7) are additional important evidence of storms, similar to previous studies (Leatherman and Williams, 1983;Sedgwick and Davis, 2003;Phantuwongraj et al, 2013;Kongsen et al, 2021). However, although foreset bedding, which is often recognized in storm deposits (Nanayama et al, 2000;Phantuwongraj et al, 2013;Kongsen et al, 2021), was not observed in the storm deposit of this area, the presence of laminated sand indicates wave pulses that carried sediments that were then deposited after the dissipation of each pulse.…”
Section: Identification Of Storm Depositssupporting
confidence: 90%
See 3 more Smart Citations
“…The parallel-laminated, inclined-laminated sand, and normal and reverse grading found in Units II, IV, and VI (Figures 3, 7) are additional important evidence of storms, similar to previous studies (Leatherman and Williams, 1983;Sedgwick and Davis, 2003;Phantuwongraj et al, 2013;Kongsen et al, 2021). However, although foreset bedding, which is often recognized in storm deposits (Nanayama et al, 2000;Phantuwongraj et al, 2013;Kongsen et al, 2021), was not observed in the storm deposit of this area, the presence of laminated sand indicates wave pulses that carried sediments that were then deposited after the dissipation of each pulse.…”
Section: Identification Of Storm Depositssupporting
confidence: 90%
“…A handheld GPS was used to provide reference points of all stations. The accuracy of distance measurement using the fine average measurement mode with a prism was ± (2 + 2 ppm X D) mm (Kongsen et al, 2021). Tidal ranges of the area were established, including the mean tide, high tide, and low tide, by converting elevation into meters amsl, following the method of Williams et al (2016).…”
Section: Topographic Survey and Stratigraphymentioning
confidence: 99%
See 2 more Smart Citations
“…1C and 2C-E). The topographical measurement was conducted by using a total station survey camera SOKKIA (SET630R) together with providing reference points of all stations by a hand-held GPS (Kongsen et al, 2021a;b). The obtained topographic values were then referenced with the tide table of Khura Buri tide gauge station for the time of measurement (Fig.…”
Section: Fieldworkmentioning
confidence: 99%